The Phenomenon of Crab Mentality Among Employees in Bandung City in Self-Development Process - Melly Maulin Purwaningwulan; Ghina Khaira (Ikatan Sarjana Komunikasi Indonesia, 2025)
The process of self-development is an essential component of an employee's self growth. However, the phenomenon of crab mentality can hinder this process, particularly in competitive work environments. Crab mentality refers to an attitude or behavior where individuals or groups tend to restrain the advancement of others due to envy or an inability to accept the success of others. This study aims to describe how the individual, societal, and organizational factors of crab mentality in employees in the self-development process. This research uses a descriptive qualitative method with a purposive sampling technique in selecting informants. Data were obtained through in-depth interviews with employees who have suffered from crab mentality. The findings of this study reveal that the phenomenon of crab mentality in the workplace emerges due to three antecedent factors. Individual Factors that capturing affective aspects such as insecurity and sociogenesis motives, Societal Factors which deal with relationships, roles, and the work atmosphere, and Organizational Factors including the role of leadership, corporate culture, and company dynamics. This research makes a significant contribution to the field of communication science, particularly in the areas of communication psychology and organizational communication.